ANALISIS KEPUASAN KONSUMEN TERHADAP PRODUK UMKM AYAM PENYET RHERE - Zainarti Zainarti; Muhammad Alfin; Mhd. Dzikry Falah Erlangga; M. Farhan Aulia Rozan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Consumer satisfaction is an important factor in ensuring the sustainability of small culinary businesses amid increasing competition. This study aims to analyze consumer satisfaction with the products of the UMKM Ayam Penyet Rhere, which offers smashed fried chicken as its main menu. The research employed a descriptive field research method. Data were collected through observation, interviews, and questionnaires distributed to consumers. The analysis focused on several aspects of satisfaction, including product quality, price, service, and consumer convenience. The results indicate that consumers are generally satisfied with the products offered, particularly in terms of taste quality and portion size relative to price. Friendly service and relatively fast serving time also contribute positively to consumer satisfaction. However, several aspects still require improvement, especially consistency of taste and supporting facilities. The findings are expected to serve as evaluation material for improving product quality and service to enhance competitiveness and customer loyalty.